Sentimento de vergonha em estudantes universitários, um estudo na moralidade - Lima, Mayara Gama de (2015)
In this study we investigate the feeling of shame based on the judgment and in the moral judgement of university students. The proposal is to develop this goal in two studies. In study 1, we conducted a survey through a questionnaire about the judgment of the presence, and/or intensity, of the feeling of shame in different situations: of exhibition, of powerlessness, of failure, as well as in moral contexts linked to generosity, honor, justice, stealing, lying and shame of shame of condition. We gathered 104 Law, and 98 Architecture and Urbanism students, totaling 202. From this results we selected the participants for the study 2, in which individual interviews based on the clinical method proposed by Piaget (1932/1994) were conducted. We pursue to investigate the moral value judgement about shame emphasizing the following aspects: the feeling conception, the moral judgement on the fictional story of honor, and justifications presented by the participants for each of these topics. In study 1, it was found that the stories involving moral values (honor, justice, stealing, lying and shame of shame of condition) reached higher percentages for the presence of shame than those involving contents that were clearly not moral (failure, powerlessness and exposure). In the first part of study 2, the data showed that the moral value judgement of shame involve contents that are equivalent to an external and internal control, being found more frequently the categories judgement and/or alien looks and self judgement, respectively. In the second part of the study 2, most participants attributed the sense of shame to the protagonist of the honor history, and the justifications allude mainly to shame as correspondent to an internal and external control, in which the most used argument refers to fact that the reaction was in the wrong way. With this work, we expect to contribute to a reflection on the relation between the feeling of shame and the moral universe of college students. Thus, emphasizing that the feeling of shame involves an internal and external control, we aim to support and promote other studies that may investigate the influence of affection in morality. We also hope that this research will provide subsidies for proposals of intervention and education in moral values that aims to virtues as central to build ethical personalities.